Toughening polylactide using epoxy-functionalized core-shell starch nanoparticles - Xinyi Dong (Elsevier, 2021)
Polylactide (PLA) is one of the most attractive biodegradable polymers owing to advantages such as high mechanical properties, biocompatibility and renewable raw material. However, wide applications of PLA are hindered by its inherent brittleness. In this work, glycidyl methacrylate (GMA)-functionalized core-shell starch-based nanoparticles (GMA-CSS) were prepared via soap-free emulsion polymerization and melt-blended with PLA. The combination of GMA and core-shell structure imparted the PLA with superior toughness. Specifically, with addition of 10 wt% GMA-CSS, the elongation at break of the PLA was improved to 449%, which was 63 times higher than that of neat PLA. Besides, the calculated toughness of PLA/GMA–CSS–10 blends was as high as 130.71 MJ/m3, which was 54 times higher than that of neat PLA. The toughening mechanism was revealed by TEM, SEM and DMA results. We envision this work establishes an efficient yet novel toughening strategy to prepare high-performance PLA and will promote the wide application in agriculture field of PLA.